1987
DOI: 10.1172/jci112776
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin stimulation of renal 25-hydroxyvitamin D-1 alpha-hydroxylase activity in hypophosphatemic mice. Evidence that the regulation of calcitriol production is not universally abnormal in X-linked hypophosphatemia.

Abstract: Hypophosphatemia (Hyp)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Nevertheless, since studies in the Hyp mouse have documented that the deranged renal enzyme activity is likely localized to the proximal convoluted tubule, the site of defective phosphate transport, the causes of these abnormalities are undoubtedly linked. Indeed, currently available evidence (31)(32)(33) suggests that the enzyme dysfunction is an acquired defect secondary to this abnormality. Thus, the apparent hormonal/metabolic defect in Hyp mice most likely indirectly influences the expressed defect in calcitriol production.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since studies in the Hyp mouse have documented that the deranged renal enzyme activity is likely localized to the proximal convoluted tubule, the site of defective phosphate transport, the causes of these abnormalities are undoubtedly linked. Indeed, currently available evidence (31)(32)(33) suggests that the enzyme dysfunction is an acquired defect secondary to this abnormality. Thus, the apparent hormonal/metabolic defect in Hyp mice most likely indirectly influences the expressed defect in calcitriol production.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, studies in Hyp mice have established such defective regulation and indicate that the abnormal function is confined to a P/PTH-responsive enzyme that may be localized to the proximal convoluted tubule (PCT; 10,11,23), the site of the abnormal phosphate transport (24)(25)(26) characteristic of the disorder. While anatomic evidence for enzyme localization has not been obtained in the mouse as it has in the rat (27,28) and fetal rabbit (29), these observations do suggest that the aberrant vitamin D metabolism in XLH is probably an acquired defect dependent on the disturbance in phosphate transport and consequent alterations of the intracellular milieu (23,30). Therefore, the recent observation that altered renal P transport in Hyp and Gy mice is due to independent mutations in a family of genes on the X chromosome (9) raises significant questions regarding the ubiquity ofthe acquired defect in vitamin D metabolism in these genetic variants of the hypophosphatemic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Nishioka et al (33) provided evidence that CT plays a role in the postnatal increase of serum 1␣,25(OH) 2 D 3 . Nesbitt et al also reported that CT stimulated renal CYP27B1 activity in hypophosphatemic mice whose serum Ca level was within the normal range (34).…”
Section: Figmentioning
confidence: 96%